Semantic memory influences episodic retrieval by increased familiarity. Issue 10 (6th July 2016) - Wang, Yujuan; Mao, Xinrui; Li, Bingcan; Lu, Baoqing; Guo, Chunyan
Abstract : The role of familiarity in associative recognition has been investigated in a number of studies, which have indicated that familiarity can facilitate recognition under certain circumstances. The ability of a pre-experimentally existing common representation to boost the contribution of familiarity has rarely been investigated. In addition, although many studies have investigated the interactions between semantic memory and episodic retrieval, the conditions that influence the presence of specific patterns were unclear. This study aimed to address these two questions. We manipulated the degree of overlap between the two representations using synonym and nonsynonym pairs in an associative recognition task. Results indicated that an increased degree of overlap enhanced recognition performance. The analysis of event-related potentials effects in the test phase showed that synonym pairs elicited both types of old/rearranged effects, whereas nonsynonym pairs elicited a late old/rearranged effect. These results confirmed that a common representation, irrespective of source, was necessary for assuring the presence of familiarity, but a common representation could not distinguish associative recognition depending on familiarity alone. Moreover, our expected double dissociation between familiarity and recollection was absent, which indicated that mode selection may be influenced by the degree of distinctness between old and rearranged pairs rather than the degree of overlap between representations.